Using granular activated carbon prepared from oil palm shell by ZnCl2 and physical activation for methane adsorption - Arami-Niya, A.; Daud, Wan Mohd Ashri Wan; Mjalli, F.S. (Elsevier, 2010)
Granular activated carbons for methane adsorption have been prepared by impregnation of oil palm shell with various solutions of ZnCl2 followed by heat treatment at 500 degrees C under a flow of nitrogen. For this precursor, large micropore volume of micropores (with a very small volume of mesopores and macropores) was obtained with intermediate ZnCl2 mass ratio. Methane capacity at 800 mmHg was in the range of 10-12 cm(3)/g. All the samples were further activated by reaction under a flow of carbon dioxide. Although such activation resulted in a decrease in the BET surface area, average pore width, micropore and pore volume (except very low impregnation ratio, X-Zn = 0.15 g/g), however, there was a 100% net increase in the methane capacity. (c) 2010 Elsevier B.V. All rights reserved.